Analysis of Good Corporate Governance Principles as an Effort to Prevent Financial Fraud at the Postgraduate Program of Sam Ratulangi University - Pinaria, Sebastian Yefta; Saerang, David P. E.; Mintalangi, Syermi S.E. (PT FORMOSA CENDEKIA GLOBAL, 2024)
Good Corporate Governance (GCG) is a set of principles aimed at enhancing transparency, accountability, and fairness in organizational management, particularly in financial contexts. Financial fraud is unethical and illegal conduct by individuals or groups to gain personal benefits at the expense of others. This study aims to analyze the application of GCG principles as an effort to prevent financial fraud in the postgraduate program at Sam Ratulangi University. The research method used is descriptive qualitative with an interview approach. Data were collected through interviews, observations, and document studies. The results show that the implementation of GCG principles at the Sam Ratulangi University postgraduate program has been quite good, but there are still some obstacles that need to be overcome to improve its effectiveness. The implementation of GCG principles has been able to increase transparency and accountability in financial management, as well as help in preventing financial fraud. This study provides recommendations to strengthen internal supervision and continuous training for stakeholders to improve understanding and application of GCG principles.